RESEARCH OF PRICING METHODS FOR BANK OPERATIONS - Yury Metel (Вестник Северо-Кавказского федерального университета, 2022)
Current rates for operations and transactions carried out by commercial banks are analyzed. Methods of forming prices for their conduct, which incorporated not only economic factors, but also the value preferences of customers, which defined by the survey the latest are considered. They were carried out in credit institutions functioning in the territory of the North Caucasus Federal District. The results are presented in the form of alternative interest rates on loans and deposits. Minimum and maximum price levels in these banking operations corresponding to the preferences of the clients are determined. Their comparison with current and received alternative tariffs are carried out.